2021
DOI: 10.1097/md.0000000000026731
|View full text |Cite
|
Sign up to set email alerts
|

A survey of surgical team members’ awareness and perceptions toward the implementation of the surgical safety checklist in gynecological and obstetrical operations

Abstract: The World Health Organization Surgical Safety Checklist was developed to improve communication in perioperative care, reduce mortality and complications of patients, and ensure the consistent use of procedures for safe surgery. Despite the increased awareness of the checklist, the implementation compliance is reported as low and the degree of completeness varies. This study aimed to explore the possible supportive factors for the effective implementation and to identify potential awareness and barriers to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…Similarly, Gong et al. (2021) found that the SSC is easy to use, and it can produce an intense improvement on the safety of surgical care (Gong et al. , 2021; Concha-Torre et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Gong et al. (2021) found that the SSC is easy to use, and it can produce an intense improvement on the safety of surgical care (Gong et al. , 2021; Concha-Torre et al.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this research illustrated that the participants found that the application of the SSC is easy and is part of hospital policy. Similarly, Gong et al. (2021) found that the SSC is easy to use, and it can produce an intense improvement on the safety of surgical care (Gong et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar disso, a percepção sobre taxa de adesão dos cirurgiões foi baixa, 77,9%, e foi alegado que a pausa para responder o questionário acaba por atrapalhar o andamento da cirurgia, significando um desperdício de tempo. Em contrapartida, os enfermeiros apresentam uma taxa de adesão de 82,4%, muito em decorrência da maior participação no processo de implementação do protocolo(GONG et al, 2021).Apesar disso, 85% dos profissionais concordam e estariam mais propensos em utilizar o checklist, principalmente se tivessem uma enfermeira experiente na organização do processo, enquanto 15% consideram que o checklist causa atrasos e 11% não acreditam na efetividade da ferramenta. Além do mais, alguns profissionais sequer tinham treinamento ou conhecimento da importância do protocolo, o que pode ser considerado barreiras para a implementação do checklist, bem como a falta de tempo e capacitação dos profissionais, contribuindo para uma baixa adesão(GONG et al, 2021).Um estudo americano observou que 55% dos eventos adversos que ocorrem em uma cirurgia é decorrente de falha humana, sendo que desses, 55% são intraoperatórios, 27% e 8% no pós e pré-operatórios, respectivamente(SILVA et al, 2020).…”
unclassified
“…Em contrapartida, os enfermeiros apresentam uma taxa de adesão de 82,4%, muito em decorrência da maior participação no processo de implementação do protocolo(GONG et al, 2021).Apesar disso, 85% dos profissionais concordam e estariam mais propensos em utilizar o checklist, principalmente se tivessem uma enfermeira experiente na organização do processo, enquanto 15% consideram que o checklist causa atrasos e 11% não acreditam na efetividade da ferramenta. Além do mais, alguns profissionais sequer tinham treinamento ou conhecimento da importância do protocolo, o que pode ser considerado barreiras para a implementação do checklist, bem como a falta de tempo e capacitação dos profissionais, contribuindo para uma baixa adesão(GONG et al, 2021).Um estudo americano observou que 55% dos eventos adversos que ocorrem em uma cirurgia é decorrente de falha humana, sendo que desses, 55% são intraoperatórios, 27% e 8% no pós e pré-operatórios, respectivamente(SILVA et al, 2020). Além disso, percebeu-se que dentre as falhas que mais geram agravos encontravam-se primeiramente na execução (erro na realização do procedimento, leitura de exames ou prescrições); em segundo, no planejamento e resolução de problemas (erros diagnósticos e recomendação…”
unclassified